BUSANA PERNIKAHAN ADAT BANJAR: WARISAN BUDAYA DALAM BINGKAI ISLAM - Laily Rahmah; Nur Adhia Fithria, Salma Saidah, Shaufiyah, Moch. Isra Hajiri (ADISAM PUBLISHER, 2025)
This study aims to examine the traditional wedding attire of the Banjar ethnic group in South Kalimantan as a representation of local culture rich in aesthetic, philosophical, and Islamic values. There are three main types of Banjar traditional bridal wear: Bagajah Gamuling Baular Lulut, Ba’amar Galung Pancar Matahari, and Babajukun Galung, each of which carries historical significance, symbolic meaning, and has undergone stylistic developments over time. Using a qualitative descriptive approach, this research employs literature studies and documentation, grounded in cultural theory and Islamic principles. The findings reveal that while early forms of these attires were influenced by Hindu-Buddhist elements, the process of Islamization has led to modifications that align with Islamic teachings, particularly in terms of modesty and covering the body (aurat). In addition to preserving traditional elements, contemporary Banjar society has adapted these outfits to accommodate hijab- wearing brides. This study highlights the importance of preserving traditional bridal attire as a cultural heritage that harmonizes with both religious values and modern sensibilities